Pojęcia muzyczne w narracji teologicznej Hansa Ursa von Balthasara - Guzek, Damian (Poznańskie Studia Teologiczne, 2012)
The article focuses on the role that musical terminology and musical masterpieces perform in the theological narration of Hans Urs von Balthasar. The author analyses the major musical terms present in Balthasar’s works and the various interpretations of those terms in the theologian’s thought. Next, he shows how Hans Urs von Balthasar uses the musical masterpieces to focus on the unspoken content of faith. The analysis confirms that Hans Urs von Balthasar treats music as an important theological source: a „locus theologicus”.